Highly efficient thermally co-evaporated perovskite solar cells and mini-modules - Li, Jia (2020)
The rapid improvement in the power conversion efficiency (PCE) of perovskite solar cells (PSCs) has prompted interest in bringing the technology toward commercialization. Capitalizing on existing industrial processes facilitates the transition from laboratory to production lines. In this work, we prove the scalability of thermally co-evaporated MAPbI3 layers in PSCs and mini-modules. With a combined strategy of active layer engineering, interfacial optimization, surface treatments, and light management, we demonstrate PSCs (0.16 cm2 active area) and mini-modules (21 cm2 active area) achieving record PCEs of 20.28% and 18.13%, respectively. Un-encapsulated PSCs retained ∼90% of their initial PCE under continuous illumination at 1 sun, without sample cooling, for more than 100 h. Looking toward tandem and building integrated photovoltaic applications, we have demonstrated semi-transparent mini-modules and colored PSCs with consistent PCEs of ∼16% for a set of visible colors. Our work demonstrates the compatibility of perovskite technology with industrial processes and its potential for next-generation photovoltaics.